Comparisons among crossbred beef cattle for growth and carcass traits - Andries, K.M.; Schalles, R.R.; Franke, D.E.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Data from 5 years of a long-term, rotational crossbreeding project were used to compare breeds for growth and carcass traits. The traits of interest were direct and maternal birth and weaning weights, gain on feed, hot carcass weight, ribeye area, marbling score, and slaughter age. Angus, Brahman, Hereford, Charolais, Simmental, and Gelbvieh breeds were involved. Simmental and Gelbvieh were used as terminal breeds, so maternal effects were not calculated for them. Brahman breeding caused an increased direct birth weight of the calves, but the maternal influence of Brahman decreased birth weight. No difference occurred in maternal weaning weight among the Angus, Brahman, Charolais, and Hereford breeds. Charolais and Simmental breeding increased gain on feed. Charolais, Simmental, and Gelbvieh breeding resulted in the heaviest hot carcass weights and largest ribeye areas. Simmental, Charolais and Angus breeding resulted in the most marbling. Hereford and Angus breeding reduced age at slaughter compared to the other breeds. All six breeds have some advantages in the traits studied. Which breed will work best depends on the production environment and goals of the producer.
Keywords: Beef; Breeds; Growth; Carcass traits